Influence of the media used in the operation of aircraft on the durability of airport cement surfaces - Piotr Nita; Małgorzata Linek (Przegląd Komunikacyjny)
Abstract: The intensification of air operations in recent years has resulted in an increase in stresses and deformations in concrete pavements. In terms of mass, dynamic and temperature interactions, these are measurable phenomena that can be determined and predicted using appropriate methods and algorithms. Another type of impact that does not occur in an avalanche-like manner on pavements is their random destruction caused by the presence and operation of exploitation media. The article presents the impact of selected measures on the change of concrete parameters and its durability in the pavement structure. The effects of this impact are significant and clearly destructive for concrete pavements. In addition to the measurable decrease in the mechanical parameters of concrete, there is an interference of media with the concrete structure, which in the presence of extreme temperatures (positive and negative) is a challenge for concrete technologists, contractors and users of airport pavements. The nature of the impact of exploitation media is varied and in most cases there is a combined effect of them on pavements. It has been shown that the operational coatings currently applied to pavements are only partially effective for these media, and learning about the nature and manner of impact makes it possible to effectively limit these unfavorable, objectively occurring phenomena. Keywords: Concrete airport pavement; Operating media